Building partnership for seed system development and diversification - Tiwari, Neha; Agrawal, Shiv Kumar; Niane, Abdoul Aziz (2025)
Nature Positive Solutions (NPS) aim to transform agrifood systems by addressing the environmental costs of industrial agriculture. CGIAR and ICAR are advancing NPS through actionable science, partnerships, and innovations to encourage smallholder farmers to adopt sustainable practices. NPS operates on five pillars: Conserve, Manage, Restore, Recycle, and Engage, promoting food security and livelihoods.